2016
DOI: 10.3839/jabc.2016.023
|View full text |Cite
|
Sign up to set email alerts
|

Effect of LED trap on controllingSitophilus zeamaisandTribolium castaneumin granary

Abstract: This study was conducted to evaluate the attraction effects of Sitophilus zeamais and Tribolium castaneum to light emitting diode (LED) trap in granary and compared with the black light bulb (BLB) trap, which is typical used in commercial trap. The red LED trap showed more attractive to S. zeamais and T. castaneum than that of the BLB. Moreover, the external condition of granary was about 1.5 times more attractive to S. zeamais and T. castaneum than the internal condition of granary. These results suggested th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 11 publications
1
2
0
Order By: Relevance
“…Finally, for both beetle species, red light was the most attractive one, with more than twice the catches than those of white and ultraviolet. These results agree with other researches conducted on the phototactic behaviour of S. zeamais ( Park et al 2015 ) and T. castaneum ( Song et al 2016a , 2016b ), where red light was the best wavelength for both species. However, different results were obtained for other beetles: S. oryzae , congeneric of S. zeamais , preferred blue and green lights, whereas red and ultraviolet lights showed similarly lower capture performance ( Jeon et al 2012 ).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Finally, for both beetle species, red light was the most attractive one, with more than twice the catches than those of white and ultraviolet. These results agree with other researches conducted on the phototactic behaviour of S. zeamais ( Park et al 2015 ) and T. castaneum ( Song et al 2016a , 2016b ), where red light was the best wavelength for both species. However, different results were obtained for other beetles: S. oryzae , congeneric of S. zeamais , preferred blue and green lights, whereas red and ultraviolet lights showed similarly lower capture performance ( Jeon et al 2012 ).…”
Section: Discussionsupporting
confidence: 92%
“…On one hand, Duehl et al (2011) found that T. castaneum was most attracted by UV wavelength and Kirkpatrick et al (1970) found that some species of stored-products beetles preferred UV over green light. On the other hand, Park et al (2015) and Song et al (2016a) found that UV light was the less attractive for S. zeamais and T. castaneum .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation